0.3666.....
If a number is repeating singly, just know it has to do with dividing by 9.
Let the number be x = 0.36.... (i)
Multiply both sides by 10.
10x = 3.66... (ii)
Equation (ii) - (i)
10x - x = 3.66 - 0.36
9x = 3.3
x = 3.3/9
x = (33/10)*(1/9)
x = 33/90
x = 11/30
The simplest fraction is 11/30
Answer:
![f(x) = 3(x -\frac{2}{3})^2 -\frac{22}{3}](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%28x%20-%5Cfrac%7B2%7D%7B3%7D%29%5E2%20-%5Cfrac%7B22%7D%7B3%7D)
The vertex is ![(\frac{2}{3}, -\frac{22}{3})](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B3%7D%2C%20-%5Cfrac%7B22%7D%7B3%7D%29)
Step-by-step explanation:
For a general quadratic function the form is:
![ax ^ 2 + bx + c](https://tex.z-dn.net/?f=ax%20%5E%202%20%2B%20bx%20%2B%20c)
For the function
![f(x) = 3x ^ 2 -4x -6](https://tex.z-dn.net/?f=f%28x%29%20%3D%203x%20%5E%202%20-4x%20-6)
Take common factor 3.
![f(x) = 3(x ^ 2 -\frac{4}{3}x - 2)](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%28x%20%5E%202%20-%5Cfrac%7B4%7D%7B3%7Dx%20-%202%29)
The values of the coefficients for the function within the parenthesis are the following:
,
, ![c = -2](https://tex.z-dn.net/?f=c%20%3D%20-2)
Take the value of b and divide it by 2. Then, the result obtained squares it.
![\frac{b}{2}= -\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%7D%7B2%7D%3D%20-%5Cfrac%7B2%7D%7B3%7D)
![(\frac{b}{2})^2=\frac{4}{9}](https://tex.z-dn.net/?f=%28%5Cfrac%7Bb%7D%7B2%7D%29%5E2%3D%5Cfrac%7B4%7D%7B9%7D)
Add and subtract ![\frac{4}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B9%7D)
![f(x) = 3([x ^ 2 -\frac{4}{3}x +\frac{4}{9}]- 2-\frac{4}{9})](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%28%5Bx%20%5E%202%20-%5Cfrac%7B4%7D%7B3%7Dx%20%2B%5Cfrac%7B4%7D%7B9%7D%5D-%202-%5Cfrac%7B4%7D%7B9%7D%29)
Write the expression of the form
![f(x) = (x-\frac{b}{2})^2 +k](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-%5Cfrac%7Bb%7D%7B2%7D%29%5E2%20%2Bk)
![f(x) = 3(x -\frac{2}{3})^2 -\frac{22}{3}](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%28x%20-%5Cfrac%7B2%7D%7B3%7D%29%5E2%20-%5Cfrac%7B22%7D%7B3%7D)
The vertex is ![(\frac{2}{3}, -\frac{22}{3})](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B3%7D%2C%20-%5Cfrac%7B22%7D%7B3%7D%29)
Answer: 7.5 cups of sugar.
Step-by-step explanation:
Add all of the above:
2+1.5+0.5+3+1.5= <u>8.5 cups of sugar</u>
<u></u>
Since Zach only needs 1 cup of sugar, subtract 1 from 8.5.
Therefore, your answer is <u>7.5 cups of sugar.</u>
Principle: Law of Exponents - Combination of product to a power & power to a power. The first is when raising a product of two integers to a power, the power is distributed to each factor. In equation it is,
(xy)^a = (x^a)(y^a)
The latter is when raising the base with a power to a power, the base will remain the same and the powers will be multiplied. In equation it is,
(x^a)(x^b) = x^ab
Check:
f(x) = 5*(16)^.33x = 5*(8*2)^0.33x = 5*(8^0.33x)(2^0.33x) = 5*(2^x)*(2^0.33x) = 5*(2^1.33x)
f(x) = 2.3*(8^0.5x) = 2.3*(4*2)^0.5x = 2.3*(2^x)(2^0.5x) = 2.3*(2^1.5x)
f(x) = 81^0.25x = 3^x
f(x) = 0.75*(9*3)^0.5x = 0.75*(3^x)*(3^0.5x) = 0.75*3^1.5x
f(x) = 24^0.33x = (8*3)^0.33x = (2^x)*(3^0.33x)
Therefore, the answer is third equation.
<em>ANSWER: f(x) = 81^0.25x = 3^x</em>